INFORMATION AND COMMUNICATION TECHNOLOGIES AS A FACTOR OF INNOVATIVE DEVELOPMENT OF AGRICULTURAL ENTERPRISES (INNOVATIVE ECONOMY, 2020)
Uniiat L.M. INFORMATION AND COMMUNICATION TECHNOLOGIES AS A FACTOR OF INNOVATIVE DEVELOPMENT OF AGRICULTURAL ENTERPRISESPurpose. The aim of the article is to study the theoretical bases and modern applied aspects of the use of information and communication technologies (ICT) in the practical activity of enterprises of agro-industrial business.Methodology of research. The theoretical and methodological basis of the study is the basic principles of economic theory and scientific development of scientists. The following methods are used in the course of the study: retrospective (analysis of economic efficiency, profitability of agricultural production in the regions of the country); monograph (coverage of statistical reporting indicators on the use of ICT in manufacturing in Ukraine); abstract and logical (theoretical generalizations and formation of conclusions, literary sources) and others.Findings. There is a clear tendency for the widespread use of ICT in the industries of the national economies of the advanced countries of the world, which contributes to the innovative development of production and a significant increase in profitability (up to 95%) in the enterprises of the processing industry and agro-industrial business. It is revealed that the use of ICT in Ukrainian enterprises is still at a low level and the main reason for this is the poor financial status of enterprises and insufficient state support. The use of ICT has been found to significantly accelerate soil analysis, determine the need and exact dosage of fertilizers, use of biological to control weeds and pests and other crop operations, which can double the crop yield. It is proved that the introduction of ICT in agro-industrial enterprises will accelerate the innovative development of the agro-industrial economy, increase the competitiveness of industries and enterprises in the market environment.Originality. A model of ICT management of making decision is proposed, which involves the availability of hardware (computers, smartphones, or iPhones and their software); Internet connection and availability of broadband access and Internet technology (social networks, website creation), through which you can actively promote your product, business, negotiate with suppliers and buyers, conduct sales and purchase operations. With the help of space technology and artificial intelligence, you can fully automate all production processes in plant and animal husbandry, eliminate the risks associated with human factors in all production processes, carry out effective planning, accounting, analysis and control of resource consumption at the enterprise, as well as take balanced management decisions.Practical value. The proposed scientific, methodological and practical developments make it possible to formulate a strategy for the effective development of ICT, which will facilitate the innovative development of agro-industrial business in a competitive environment.Key words: information and communication technologies; digitalization of agro-industrial enterprises; innovations; development strategy; efficiency; profitability; competition; agro-industrial business.
Keywords: Key words; information and communication technologies; digitalization of agro-industrial enterprises; innovations; development strategy; efficiency; profitability; competition; agro-industrial business.